PSYCHOLOGICAL TREATMENT APPROACHES FOR OBSESSIVE-COMPULSIVE DISORDERS DURING THE COVID-19 PANDEMIC - Yunuskhodjaeva, Khilolakhon; Ibodullayev, Zarifboy; Maxamatjanova, Nodira (PT. Antis International Publisher, 2024)
This study investigates the psychocorrection of obsessive-compulsive disorders (OCD) exacerbated by the COVID-19 pandemic. The research involved a cohort of 40 patients diagnosed with OCD, whose symptoms intensified during the pandemic. Participants underwent a series of psychocorrective interventions, including cognitive-behavioral therapy (CBT), exposure and response prevention (ERP), and mindfulness-based techniques. The efficacy of these interventions was assessed through pre- and post-treatment evaluations using standardized OCD symptom scales and patient self-reports. Results indicated significant improvements in OCD symptoms and overall mental well-being. Patients reported reduced anxiety and compulsive behaviors, and increased ability to manage obsessive thoughts. The findings suggest that targeted psychocorrective strategies can be effective in alleviating pandemic-induced exacerbations of OCD, highlighting the importance of adapting therapeutic approaches to current global health crises